Delay in calling for help during myocardial infarction: reasons for the delay and subsequent pattern of accessing care. Issue 2 (1st August 2000) - Leslie, W S; Urie, A; Hooper, J; Morrison, C E
Abstract : OBJECTIVE: To determine the reasons for delay in calling for help during acute myocardial infarction and the reasons for choice of first medical contact. DESIGN: Review of routine medical records and one to one semi-structured interviews. SETTING: Community survey in city of Glasgow, north of the river Clyde. PATIENTS: 228 men and 85 women aged between 25 and 65 years, respectively, who survived acute myocardial infarction between October 1994 and December 1996. RESULTS: Only 25% of the subjects made a call for help within one hour of the onset of coronary symptoms; in 40% the delay was greater than four hours. Symptoms were not recognised as coronary in origin in the majority of cases. In all cases where delay was more than one hour the main reasons for the delay were thinking that symptoms would go away or that they were not serious. Requesting the attendance of a general practitioner was the first course of action in the majority of cases (55%); the main reason given was that the patient believed this should always be the first course of action. Reluctance to call the emergency services reflected the belief that the symptoms were not serious enough to warrant an ambulance. CONCLUSIONS: Strategies to reduce patient delay times in this deprived urban population must focus on educating the public on the recognition and diversity of coronary symptoms and the benefits of presenting promptly to hospital by way of the emergency ambulance service.